A Proposed Model for Improving Battlefield Analgesia Training: Post-Graduate Medical Officer Pain Management Day. Issue 3 (1st September 2012) - Davey, Colette; Mieville, KE; Simpson, R; Aldington, D
Abstract : In response to increasing awareness of the need to improve Post Graduate Medical Officers training in the use of analgesics when on Operations and exercises, a new "Pain Day" format has been realised and included in the Post Graduate Medical Officers Course. This article discusses the format of the Pain Day; gives evidence of the feedback received; explores areas where further training may be required and suggests mechanisms through which improved training could be provided throughout the armed forces medical community.